Movement patterns of snow leopard (Panthera uncia) around kills based on GPS location clusters - Grönberg, Elin (2011)
Research concerning movement patterns of wild animals has been advancing since GPS technology arrived. But studying the snow leopard (Panthera uncia) is still difficult because of the harsh territory it inhabits in Central Asia. This study took place in south Gobi, Mongolia, and aimed to estimate the time spent at kills and the maximum distance away from kills between visits. Snow leopards were monitored with GPS collars that took a location every five or seven hours. Potential kill sites were established by identifying clusters of GPS-locations in ArcGIS and visited in the field for confirmation. ArcGIS was used to calculate the distance between cluster and GPS-locations. I used two buffer zones (100 m and 500 m radius) to define the time snow leopards spent at kills. It was found that snow leopard age and prey category affected time spent at kills and also that snow leopard sex together with prey category affected the maximum distance moved away from kills between visits. Season had no significant effect on either time at kills or distance moved away from kills between visits. Snow leopards spent on average 3.2 days at their kills in the 100 m buffer zone and 3.5 days at their kills in the 500 m buffer zone. Subadults stayed longer at kills than adults and animals of both age categories spent longer time on larger prey. The mean maximum distance moved away from kills between visits was 179 m in the 100 m buffer zone and 252 m in the 500 m buffer zone. Female snow leopards moved further away from kills between visits than male snow leopards. Both the number of days spent on kills and maximum distance moved away from kills between visits increased when kills consisted of more than one animal. This study has provided some basic information on snow leopard behaviors around their kills but also highlights the need to monitor more snow leopards before more solid conclusions can be drawn as this study was based on based on a relatively small sample.